Barriers to Blockchain Technology Adoption in the Halal Supply Chain: Insights from Manufacturers and Regulatory Authorities - Azhari Julian, Fajar; Ameliana, Elsa (SocioHumania: Journal of Social Humanities Studies, 2024)
This study aims to identify and analyze the barriers to blockchain technology adoption within the halal supply chain, focusing on insights from manufacturers and regulatory authorities. Using a library research approach, the study synthesizes existing literature and relevant case studies to explore key challenges, including technological readiness, regulatory constraints, cost implications, and stakeholder collaboration. The findings reveal that lack of awareness, inadequate infrastructure, and misalignment of regulatory frameworks significantly hinder blockchain integration in halal supply chains. These insights underscore the need for enhanced education, policy harmonization, and investment in technology to facilitate adoption. The study’s implications highlight pathways for stakeholders to overcome these barriers, thereby enhancing transparency and trust in the halal supply chain.